2013
DOI: 10.1155/2013/850865
|View full text |Cite
|
Sign up to set email alerts
|

External Ophthalmomyiasis Caused by a Rare Infesting Larva,Sarcophaga argyrostoma

Abstract: Purpose. External ophthalmomyiasis (EO) is caused by infesting larvae belonging to various species of flies. Most documented cases result from sheep (Oestrus ovis) and Russian (Rhinoestrus purpureus) botfly larvae, but we recently discovered a rare case of EO caused by flesh fly (Sarcophaga argyrostoma) larvae. Here, we report the case of a patient with EO who had been hospitalized and sedated for 1 week because of unrelated pneumonia. Methods. Case report. Results. A total of 32 larvae were removed from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Thus, it should be considered as Ban occupational disease^among farmer and shepherds. Myiasis is recorded frequently in tropical and semitropical countries, especially in rural areas where people live in close contact with their domestic animals (Graffi et al 2013;Demirel Kaya et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it should be considered as Ban occupational disease^among farmer and shepherds. Myiasis is recorded frequently in tropical and semitropical countries, especially in rural areas where people live in close contact with their domestic animals (Graffi et al 2013;Demirel Kaya et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, myiasis infestation occurs preferably during the summer, a favorable period for the reproduction of the flies (Graffi et al 2013;Demirel Kaya et al 2014). All cases in the present study occurred during the summer, when the density of fly population is the greatest, like many other reports (Sesterhenn et al 2009;Maleki-Ravasan et al 2014;Demirel Kaya et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Verma et al (1990) reported the association of ophthalmomyiasis caused by C. bezziana with the virus Herpes zoster. Another rare case of ophthalmomyiasis by Sarcophaga argyrostoma was reported by (Graffi et al 2013). The elk throat botfly, Cephenemyia ulrichii, had also been reported to cause human ophthalmomyiasis from Finland (Mikkola et al 1982).…”
Section: Ophthalmomyiasismentioning
confidence: 99%
“…The robustness of the coxI gene as a diagnostic marker to lay the groundwork for identification of these three species of Sarcophaga has been demonstrated [ 21 , 26 ]. Sarcophaga argyrostoma has been identified using a coxI sequence in an elderly patient with an external ophthalmomyiasis (with 97% identity) [ 6 ] and very recently in a tracheotomized child's surgical wound (with an identity of 100%) [ 8 ]. In the present study, the involvement of S. argyrostoma in the wound myiasis is confirmed with 99% identity.…”
Section: Discussionmentioning
confidence: 99%